Chemical Sensing: Microlandscaping of Au Nanoparticles on Few‐Layer MoS2 Films for Chemical Sensing (Small 15/2015). Issue 15 (April 2015) - Lu, Junpeng; Lu, Jia Hui; Liu, Hongwei; Liu, Bo; Gong, Lili; Tok, Eng Soon; Loh, Kian Ping; Sow, Chorng Haur
<x xml:space="preserve">Abstract</x> Micro landscaping of gold nanoparticles on a thin MoS2 film is achieved via dipping a laser‐activated MoS2 film into gold chloride. On page 1792, the activated micropatterns are first created on the MoS2 film by C. H. Sow and co‐workers using a scanning focused laser beam. When the activated film is subsequently immersed in gold chloride for only 10 s, gold nanoparticles are found on the modified micropatterns. These decorated MoS2 micropatterns turn out to be sensitive detectors for aromatic molecules via the production of strong SERS signals. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>